2013
DOI: 10.1016/j.neuro.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Valeriana officinalis attenuates the rotenone-induced toxicity in Drosophila melanogaster

Abstract: In this study, we investigated the potential protective effects of Valeriana officinalis (V. officinalis) against the toxicity induced by rotenone in Drosophila melanogaster (D. melanogaster). Adult wild-type flies were concomitantly exposed to rotenone (500 μM) and V. officinalis aqueous extract (10mg/mL) in the food during 7 days. Rotenone-fed flies had a worse performance in the negative geotaxis assay (i.e. climbing capability) and open-field test (i.e. mobility time) as well as a higher incidence of morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 40 publications
3
50
0
Order By: Relevance
“…induction of a temporal and concentration dependent locomotor phenotype (as evident by significant impaired climbing ability). These data are consistent with findings of several other researchers (Sudati et al 2013;Laurent et al 2013) and our findings in the fly model (Girish and Muralidhara, 2012). Interestingly, we demonstrate substantial improvement of ROT-induced early mortality as well as locomotor impairment with WS -enrichment.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…induction of a temporal and concentration dependent locomotor phenotype (as evident by significant impaired climbing ability). These data are consistent with findings of several other researchers (Sudati et al 2013;Laurent et al 2013) and our findings in the fly model (Girish and Muralidhara, 2012). Interestingly, we demonstrate substantial improvement of ROT-induced early mortality as well as locomotor impairment with WS -enrichment.…”
Section: Discussionsupporting
confidence: 94%
“…In recent times, Drosophila system is extensively employed not only to obtain basic mechanistic data on the pathophysiology of several neurodegenerative diseases, but also as a primary platform to screen various putative phytochemicals for their neuromodulatory potency against experimentallyinduced neurodegeneration (Laurent et al 2013;Sudati et al 2013). Rotenone (ROT), a well-established mitochondrial toxin is often used as a model chemical, since it reproduces some important aspects of PD pathology both in Drosophila and rodent models (Coulom and Birman, 2004;Canon and Greenamyere 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These flies were grown in standard food medium for D. melanogaster containing 1, 2.5, 5 and 10 mg/ml VoE, 8 mM ME or a combination of both 8 mM ME + 10 mg/ml VoE. The choice of V. officinalis aqueous extract concentrations was based on previous observations by Sudati et al (2013) which showed that V. officinalis aqueous extracts in the range of 5 -20 mg/ml did not cause overt signals of toxicity in flies. Coulom and Birman (2004) showed that a 5 mM concentration of the antioxidant melatonin was able to prevent both locomotor deficits and neuron degeneration in Drosophila.…”
Section: Ring Assaymentioning
confidence: 99%